Entrepreneurship Education and the Role of Technology in Driving Business Innovation - Puspita Puji Rahayu; Isti Mayasari; Qurnia Fitriyatinur; Menik Tetha Agustina (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Increasing business innovation is the main key in facing increasingly fierce competition in the current era of globalisation and information technology. One factor that plays a key role in driving business innovation is entrepreneurship education. This study aims to investigate the relationship between entrepreneurship education and the role of technology in driving business innovation. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from various sources. The study results show that entrepreneurship education and the role of technology in fostering business innovation are two elements that are highly related and mutually supportive. Effective entrepreneurship education should include technology as an integral part of its curriculum, enabling students to understand how technology can be used in various aspects of business. With this understanding, they can develop practical skills, think creatively, collaborate and innovate with the support of technology, thus being better equipped to face challenges in an increasingly digital and competitive business world. The limitation of this research is that it is a literature review, so it does not involve primary data collection or field research. Therefore, the findings are descriptive and based on existing information in the literature accessed.